1982
DOI: 10.1111/j.1532-5415.1982.tb03384.x
|View full text |Cite
|
Sign up to set email alerts
|

A Long‐term Geriatric Teaching Ward in an Acute‐care Hospital: A Three‐year Experience

Abstract: The development and management of a long-term geriatric ward in an acute-care teaching hospital are described. Structure, function, and costs are discussed, and issues of service and medical education are emphasized. A full geriatric team (physician, nurse, social worker, physiotherapist, and occupational therapist) assessed 165 long-term patients in the general wards of the hospital and accepted 98 for admission to the new long-term geriatric ward. Of these, 31 were discharged; 29 per cent went to a facility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

1983
1983
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 5 publications
1
11
0
Order By: Relevance
“…Finally, although various disease classification models exist (ICD 9, etc. ), which may or may not have been used by the authors of other studies, we felt that this left out the “grey” area of the problems that are specific to geriatrics, such as falls, incontinence, iatrogenic events, and confusional states 24,25 . The high prevalence rates for these geriatric problems found in our sample are a reflection of the need to address the “geriatric giants” even in the ED setting, a finding similar to that of others 26,27 …”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Finally, although various disease classification models exist (ICD 9, etc. ), which may or may not have been used by the authors of other studies, we felt that this left out the “grey” area of the problems that are specific to geriatrics, such as falls, incontinence, iatrogenic events, and confusional states 24,25 . The high prevalence rates for these geriatric problems found in our sample are a reflection of the need to address the “geriatric giants” even in the ED setting, a finding similar to that of others 26,27 …”
Section: Discussionsupporting
confidence: 60%
“…The long LOS, both in the ED and within the hospital for those subsequently admitted, can be explained by reference to the specific situation of the SMBDJGH as described by Clarfield 24 . Because of a combination of an extremely aged catchment population in combination with a dire shortage of long‐term beds in that area, nearly 25% of the hospital's acute care beds are utilized by older patients awaiting placement.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative studies of hospitalized elderly patients involve either a geriatric evaluation unit, 6–8 chronic care hospitals, 9–10 or consultation services 13–15 . Geriatric evaluation units are usually geographically defined beds in an acute or chronic care hospital and provide comprehensive geriatric assessment and rehabilitation for patients who are selected after admission from general medical wards.…”
Section: Discussionmentioning
confidence: 99%
“…Fewer than 10% of all acute admissions to the VA medical center where the study took place were considered to be candidates for the geriatric evaluation unit 16 . Other studies in geriatric evaluation units or chronic care hospitals were either descriptive in nature 8–9 or contained no data concerning length of stay 10–11 . A randomized study by Shamian et al 12 involving a chronic care hospital population gave no data on length of stay.…”
Section: Discussionmentioning
confidence: 99%
“…Acute care geriatric units functioning under the Medicare PPS have compelling incentives for focusing on the efficiency as well as the quality of acute care as measures of success, as emphasized by recent survey studies 3 . Since the frail elderly have relatively long hospital lengths of stay (LOS) throughout the world, 4, 5 these patients generally create financial losses under the Medicare Diagnosis Related Groups (DRG) system 6, 7 . Furthermore, some studies have indicated that the introduction of the PPS was associated with specific declines in quality of care for the frail elderly, although improvements in the process of care and even mortality have also been noted 8–11 .…”
mentioning
confidence: 99%